Impacts of oil price on bank profitability - Chen, Yee Jing; Chong, Koor Xuan; Lian, Jian Yang; Ng, Pooi Ling; Teo, Wan Yun (2019)
This project is specifically for academic purpose. We come across this study as we notice some strange and noteworthy effects of the oil price. Lots of researches has been conducted on effects of macroeconomic conditions on the bank profitability where the concern we conducting this research is no longer trying to find out the impacts of macroeconomic conditions on the bank profitability. This study is concerning on the impact of oil price on the bank profitability, in other words, what how oil price influence bank profitability. Firstly is there a significant relationship between bank profitability namely ROA and ROE and oil price? Secondly is there a dynamic effect of oil price to bank profitability namely ROA and ROE? By understanding these two questions, it might help in constructing a better policy that will better shaping the country towards the economic condition.